The role of relationships in start-up development. (3rd October 2019) - Mattsson, Jan; Helmersson, Helge; Standing, Craig
Abstract: Relationships are important in the business start-up phase for a variety of reasons. Internal relationships can support knowledge exchange that determines the business model development and external relationships can facilitate a wide range of opportunities, support and insights. The paper explains the key relationships experienced by the founding team of a recently formed Swedish digital trading platform. Data were gathered through a self-reporting diary approach based on the Critical Incident Technique format and texts were analysed by the Pertex text-analytic software. The findings explain how important relationships were formed during the initial start-up period targeting international expansion. Interaction with early adopters enabled a rapid evolution of the business platform with the aim to build a community of users to support development.